KEPEKAAN ANTIMIKROBA KULTUR DARAH DI SEPSIS NEONATAL - Tajuddin Noor; Nurhayana Sennang; Benny Rusli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Sepsis was one of the morbidity and mortality causes in neonatal. The diagnosis and treatment requires the bacterial identification and selection of sensitive antimicrobials. The aim of this study was to know the bacterial pattern and antimicrobial sensitivity of blood culture in the suspected neonatal sepsis patients who were treated at NICU in Dr.Wahidin Sudirohusodo Hospital Makassar. A retrospective study was conducted with secondary data from the culture and antimicrobial susceptibility test between the period of June 2010−July 2011. In this present study was found that from the total 91 blood culture isolates, bacteria Gram-negative group was 85.7% and Grampositive was 14.3% and the isolate encountered in order of frequency were Alkali genes faecalis 50.5%, Klebsiella pneumonia 25.3%, and Staphylococcus epidermidis 9.9%. In the Gram-negatives group, the isolate often encountered were Alkali genes faecalis 59.0%, Klebsiella pneumonia 29.4% and Enterobacter spp 6.4% while in the Gram-positive group were found Staphylococcus epidermidis 69.2% and Staphylococcus saprophytic 23.1%. The more sensitive antimicrobal that belong to Gram-negative group were Meropenem 94.4%, Levofloxacin 92.1%, and Ceftazidime 77.0% while the more resistant were Ampicillin 94.6%, Gentamycin 89.1% and Cefuroxime 82.7%. The more sensitive antimicrobal that belong to Gram-positive group were Vancomycin and Chloramphenicol 91.7% and Novobiosin 76.9% while the more resistant were Gentamycin and Ceftriaxone 100.0% and Amoxicillin 91.7%. Based on this study it can be concluded that Gram-negative aerobe bacteria was more common than the Gram-positive one. Meropenem, Levofloxacin and Ceftazidime antimicrobal were high sensitive to Gram-negative while Vancomycin, Chloramphenicol, and Novobiocin were high sensitive to Gram-positive. The resistance of Ampicillin and Gentamycin were found in both bacterially groups of sepsis suspected neonatal patients in NICU